2022
DOI: 10.1002/ps.6795
|View full text |Cite
|
Sign up to set email alerts
|

Fusarium graminearumFgSdhC1 point mutation A78V confers resistance to the succinate dehydrogenase inhibitor pydiflumetofen

Abstract: BACKGROUND Fusarium head blight (FHB) caused by Fusarium graminearum complex (Fg) is a devastating disease of cereal crops worldwide. The succinate dehydrogenase inhibitor, pydiflumetofen, was registered for management of FHB in China in 2019. Previously, laboratory‐induced pydiflumetofen‐resistant (PyR) mutants of Fg have been characterized. However, resistance situation of Fg to pydiflumetofen in the field remains largely unknown. RESULTS After screening 6468 isolates of Fg from various regions of China, six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 46 publications
1
28
0
Order By: Relevance
“…Similar results have been reported in previous studies, namely, that F. graminearum isolates recovered in the field were spontaneously resistant to pydiflumetofen with 9×10 –4 resistance frequency . After the 10th subculture, the RF of mutants was still greater than 200, and this was attributed to a high resistance level though lower than that of the first generation.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Similar results have been reported in previous studies, namely, that F. graminearum isolates recovered in the field were spontaneously resistant to pydiflumetofen with 9×10 –4 resistance frequency . After the 10th subculture, the RF of mutants was still greater than 200, and this was attributed to a high resistance level though lower than that of the first generation.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies had already shown that several point mutations in the SDH proteins of Fusarium species could cause SDHIs resistance. Point mutation A78V in FgSdhC 1 confers resistance to pydiflumetofen in F. graminearum, 26 while point mutations R86C or T77I in FgSdhC 2 and A-to-T mutation at the −57 bp of the 5′ untranslated region (5′-UTR) of FgSdhC 1 confers resistance to flubeneteram. 16 Furthermore, FaSdhB H248Y , FaSdhC 1 A64V , or FaSdhC 1 R67K mutations are associated with the resistance of F. asiaticum to pydiflumetofen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Alternaria alternata, the mutations SdhB H277Y/R/L , SdhC H134R,S135R , and SdhD D123E,H133R/P/T were verified to confer resistance to boscalid. , The mutations FaSdhB H248Y and FaSdhC 1 A64V,R67K conferred resistance to pydiflumetofen in Fusarium asiaticum . The mutations FgSdhC 1 A78V and FgSdhC 2 A83V,R86C,R86H conferred resistance of Fusarium graminearum to pydiflumetofen, , and the mutations FgSdhC 2 T77I,R86C or −57 bp A to T mutation in the 5′ UTR of FgSdhC 1 conferred resistance of F. graminearum to flubeneteram .…”
Section: Discussionmentioning
confidence: 98%
“…38,39 The mutations FaSdhB H248Y and FaSdh-C 1 A64V,R67K conferred resistance to pydiflumetofen in Fusarium a s i a t i c u m . 3 1 T h e m u t a t i o n s F g S d h C 1 A 7 8 V a n d FgSdhC 2 A83V,R86C,R86H conferred resistance of Fusarium graminearum to pydiflumetofen, 40,41 and the mutations FgSdhC 2 T77I,R86C or −57 bp A to T mutation in the 5′ UTR of FgSdhC 1 conferred resistance of F. graminearum to flubeneteram. 42 FfSdhB H248L/Y and FfSdhC 2 A83V are conserved mutated positions in homologous proteins of other phytopathogenic microorganisms, 31,37−41 indicating that there is high relevance between these amino acid substitutions and SDHI resistance in different fungal species.…”
Section: ■ Discussionmentioning
confidence: 99%